Association of Teen Dating Aggression With Risk Behavior and Academic Adjustment - Datta, Pooja (Journal of interpersonal violence, 2022)
This study constructed a six-item Teen Dating Aggression (TDA) scale, investigated the prevalence of TDA in a statewide sample, and identified associations between TDA and high-risk behaviors and academic adjustment. Based on a review of literature, TDA included physical harm, threats to harm, verbal aggression, forced sexual contact, coercion to use alcohol or drugs, and harassment after the relationship ended. The sample consisted of 32,428 students (Grades 9?12) in 320 Virginia high schools who completed a statewide school climate survey. Participation rates were 99% for schools and 80.5% for students. Confirmatory factor analysis and hierarchical regression analyses investigated the associations between TDA and high-risk behaviors and poor academic adjustment. School fixed-effects analyses accounted for school-level influences in student responses. Nearly four in 10 students (39%) reported experiencing at least one form of dating aggression in the past year. The 12,596 students who experienced TDA (40%) in the past year reported more marijuana use (26% vs. 13%), alcohol use (40% vs. 22%), fighting (13% vs. 5%), suicidal ideation (31% vs. 13%), and suicide attempts (17% vs. 5%), as well as lower school engagement, educational aspirations, and grades than 19,832 students who dated without TDA. The current study emphasized the need for dating aggression to be a focus of secondary school prevention programs due its associations with poorer academic performance, high-risk behavior with potentially serious mental health consequences. Accurate assessment of TDA can also guide the evaluation of intervention programs that target TDA.